High-thermal-conductivity adhesive tape and preparation method thereof
By optimizing the combination and chemical modification of glue mucus, the high -conductive tape is prepared, solving the lack of the existing materials between thermal conductivity and bonding performance, and realized the high -efficiency thermal management and reliable bonding of LED devices.
Patent Information
- Application Number
- CN202411541816.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-21
AI Technical Summary
While improving the bonding performance, existing LED bonding materials ignore thermal conductivity, resulting in equipment overheating problems; while materials that rely solely on high thermal fillers have insufficient bonding strength and durability.
Through scientifically optimizing the combination of glue mucus and chemical modification, combined with glue mucus A and B, coated on both sides of the PET substrate, and cured by thermalization to prepare high -conductive tape. Adhesive mucous emulsion A contains epoxy nanox nitride, which provides high thermal conductivity, whileulus B to enhance the initial adhesion and peeling strength.
The highly thermally conductive tape achieves an excellent balance between high thermal conductivity and bonding performance, ensuring efficient thermal management and reliable bonding of LED equipment. It is suitable for LED lamps, displays, backlight modules and other scenarios.
Smart Images

Figure BDA0005112964760000111
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesive tapes, and in particular to a high thermal conductivity adhesive tape and a preparation method thereof. Background Art
[0002] In the modern electronics industry, especially in the field of LED technology, how to effectively manage the generation and dissipation of heat has become a core issue that affects product performance and life. As a high-efficiency light source, LED generates a large amount of heat energy during operation. If it cannot be effectively managed, this heat energy will accumulate inside the LED, resulting in reduced efficiency, increased losses, and possible premature failure. Therefore, high thermal conductivity double-sided tape, as a key solution, can promote effective heat conduction while fixing LED components, which is crucial to ensuring the reliability and performance of LED equipment.
[0003] Traditional LED adhesive materials usually only focus on their adhesive properties, while ignoring thermal conductivity. Materials that simply improve adhesive properties may cause equipment overheating due to lack of sufficient thermal management capabilities. At the same time, adhesive materials that only rely on high thermal conductivity fillers to improve thermal conductivity often have problems with insufficient bonding strength and durability. Due to the complexity of the working environment of LED devices, including high temperature, vibration, and chemical corrosion, the preparation of an adhesive tape that can provide both high bonding strength and excellent thermal conductivity is a demand for current technological development. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a high thermal conductivity tape and a preparation method thereof, so as to ensure that the tape has excellent bonding performance while having high thermal conductivity.
[0005] Based on the above purpose, the present invention provides a high thermal conductive tape, which is obtained by mixing 8 parts of adhesive emulsion A and 1-3 parts of adhesive emulsion B by weight, coating them on both sides of a PET substrate, and thermally curing them.
[0006] Furthermore, the adhesive emulsion A is obtained by emulsion polymerization from the following raw materials in parts by weight: 60-90 parts of methyl methacrylate, 200-400 parts of styrene, 80-120 parts of isooctyl acrylate, 15-25 parts of ethyl acrylate, 10-20 parts of hydroxyethyl acrylate, 100-200 parts of epoxidized nano boron nitride dispersion, 4-6 parts of emulsifier, 100-150 parts of initiator aqueous solution and 80-160 parts of deionized water.
[0007] Furthermore, the adhesive emulsion B is obtained by emulsion polymerization from the following raw materials in parts by weight: 60-90 parts of methyl methacrylate, 200-400 parts of n-butyl acrylate, 80-120 parts of isooctyl acrylate, 15-25 parts of ethyl acrylate, 10-20 parts of hydroxyethyl acrylate, 4-6 parts of emulsifier, 100-150 parts of initiator aqueous solution and 80-160 parts of deionized water.
[0008] Furthermore, the preparation method of the epoxidized nano-boron nitride dispersion is as follows:
[0009] (1) using silane coupling agent KH-560 to modify nano boron nitride to obtain epoxidized nano boron nitride;
[0010] (2) Dispersing the epoxidized nano-boron nitride in deionized water and ultrasonicating for 20-40 minutes to obtain an epoxidized nano-boron nitride dispersion.
[0011] Preferably, in step (1), the weight ratio of the silane coupling agent KH-560 to the nano-boron nitride is 1-5:50.
[0012] Preferably, in step (2), the weight ratio of epoxidized nano-boron nitride to deionized water is 1:2.
[0013] Preferably, the emulsifier is a mixture of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether in a weight ratio of 1:3-5.
[0014] Preferably, the initiator aqueous solution is prepared as follows: adding ammonium persulfate into deionized water and stirring for 20-40 minutes to obtain an initiator aqueous solution;
[0015] Preferably, the weight ratio of the ammonium persulfate to deionized water is 1:25.
[0016] Preferably, the preparation method of the adhesive emulsion A is as follows: add the emulsifier to deionized water, stir for 20-40 minutes, then add methyl methacrylate, styrene, isooctyl acrylate, ethyl acrylate and hydroxyethyl acrylate, stir for 10-20 minutes, heat to 80-90°C, add the initiator aqueous solution, then dropwise add the epoxidized nano boron nitride dispersion, and after the dropwise addition is completed, stir the reaction for 5-7 hours to obtain the adhesive emulsion A.
[0017] Preferably, the preparation method of the adhesive emulsion B is as follows: add the emulsifier to deionized water, stir for 20-40 minutes, then add methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate and hydroxyethyl acrylate, stir for 10-20 minutes, heat to 80-90°C, add the initiator aqueous solution, stir and react for 5-7 hours to obtain the adhesive emulsion B.
[0018] Furthermore, the present invention also provides a method for preparing a high thermal conductive tape, comprising the following steps: mixing adhesive emulsion A and adhesive emulsion B, stirring for 10-20 minutes, applying them on both sides of a PET substrate using an applicator, drying them in an oven at 115-125°C for 5-7 hours, covering them with a release film, and winding and slitting them to obtain a high thermal conductive tape.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides a high thermal conductivity tape, which achieves an excellent performance balance by scientifically optimizing the combination of adhesive emulsions and chemical modifications. First, the tape overcomes the limitations of using a single emulsion by combining adhesive emulsions A and B. In adhesive emulsion A, epoxide boron nitride provides high thermal conductivity, while emulsion B enhances initial adhesion and peel strength. The protective layer formed by the reaction of the epoxy groups in latex A with the hydroxyl groups in hydroxyethyl acrylate enhances the cohesion and stability of the adhesive particles; in the later thermal curing stage, these epoxy groups cross-link with the hydroxyl groups in emulsion B to construct a uniform thermal conductive network, while significantly improving the bonding strength.
[0021] The present invention ensures that the material has excellent bonding properties while having high thermal conductivity through the combination of styrene (hard monomer) and n-butyl acrylate (soft monomer). The adjustment of this chemical formula retains the high initial adhesion, lasting adhesion and excellent peel strength of the tape, and can remain stable even under extreme temperature conditions. The final prepared tape is particularly suitable for LED components, such as lamps, display screens and backlight modules, which require efficient thermal management and reliable bonding, and provides excellent heat dissipation paths and bonding stability for these applications. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0023] The nano boron nitride in the specific implementation manner of the present invention was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. with the item number of B140007.
[0024] Embodiment 1:
[0025] (1) Add 1 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 20 min, then heat to 45° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 3 h, wash, and dry to obtain epoxidized nano boron nitride;
[0026] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 30 min to obtain an epoxidized nano-boron nitride dispersion;
[0027] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 20 min to obtain an initiator aqueous solution;
[0028] (4) 1 g of sodium dodecyl sulfate and 3 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 80 g of deionized water, stirred for 20 min, and then 60 g of methyl methacrylate, 200 g of styrene, 80 g of isooctyl acrylate, 15 g of ethyl acrylate and 10 g of hydroxyethyl acrylate were added, stirred for 10 min, heated to 80° C., 100 g of initiator aqueous solution was added, and then 100 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 5 h to obtain adhesive emulsion A;
[0029] (5) 1 g of sodium dodecyl sulfate and 3 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 180 g of deionized water, stirred for 20 min, and then 60 g of methyl methacrylate, 200 g of n-butyl acrylate, 80 g of isooctyl acrylate, 15 g of ethyl acrylate and 10 g of hydroxyethyl acrylate were added, stirred for 10 min, heated to 80° C., 100 g of initiator aqueous solution was added, and stirred for reaction for 5 h to obtain adhesive emulsion B;
[0030] (6) 400 g of adhesive emulsion A and 50 g of adhesive emulsion B were mixed, stirred for 10 min, applied to both sides of the PET substrate using a coater, dried in an oven at 115° C. for 5 h, covered with a release film, and rolled and slit to obtain a high thermal conductive tape.
[0031] Embodiment 2:
[0032] (1) Add 2.5 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 30 min, then heat to 50° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 4 h, wash, and dry to obtain epoxidized nano boron nitride;
[0033] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 20 min to obtain an epoxidized nano-boron nitride dispersion;
[0034] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 30 min to obtain an initiator aqueous solution;
[0035] (4) 1 g of sodium dodecyl sulfate and 4 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of styrene, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and then 150 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 6 h to obtain adhesive emulsion A;
[0036] (5) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and stirred for reaction for 6 h to obtain adhesive emulsion B;
[0037] (6) 400 g of adhesive emulsion A and 100 g of adhesive emulsion B were mixed, stirred for 15 min, applied to both sides of the PET substrate using a coater, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain a high thermal conductive tape.
[0038] Embodiment 3:
[0039] (1) Add 5 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 40 min, then heat to 55° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 5 h, wash, and dry to obtain epoxidized nano boron nitride;
[0040] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 40 min to obtain an epoxidized nano-boron nitride dispersion;
[0041] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 40 min to obtain an initiator aqueous solution;
[0042] (4) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 160 g of deionized water, stirred for 40 min, and then 90 g of methyl methacrylate, 400 g of styrene, 120 g of isooctyl acrylate, 25 g of ethyl acrylate and 20 g of hydroxyethyl acrylate were added, stirred for 20 min, heated to 90° C., 150 g of initiator aqueous solution was added, and then 200 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the reaction was stirred for 7 h to obtain adhesive emulsion A;
[0043] (5) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 160 g of deionized water, stirred for 40 min, and then 90 g of methyl methacrylate, 400 g of n-butyl acrylate, 120 g of isooctyl acrylate, 25 g of ethyl acrylate and 20 g of hydroxyethyl acrylate were added, stirred for 20 min, heated to 90° C., 150 g of initiator aqueous solution was added, and stirred for reaction for 7 h to obtain adhesive emulsion B;
[0044] (6) 400 g of adhesive emulsion A and 150 g of adhesive emulsion B were mixed, stirred for 20 min, applied to both sides of the PET substrate using an applicator, dried in an oven at 125° C. for 7 h, covered with a release film, and rolled and slit to obtain a high thermal conductive tape.
[0045] Comparative Example 1:
[0046] The difference between Comparative Example 1 and Example 2 is that the adhesive emulsion A is directly coated on both sides of the PET substrate;
[0047] The specific steps are as follows:
[0048] (1) Add 2.5 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 30 min, then heat to 50° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 4 h, wash, and dry to obtain epoxidized nano boron nitride;
[0049] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 20 min to obtain an epoxidized nano-boron nitride dispersion;
[0050] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 30 min to obtain an initiator aqueous solution;
[0051] (4) 1 g of sodium dodecyl sulfate and 4 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of styrene, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and then 150 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 6 h to obtain adhesive emulsion A;
[0052] (5) 500 g of adhesive emulsion A was applied to both sides of the PET substrate using an applicator, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain an adhesive tape.
[0053] Comparative Example 2:
[0054] The difference between Comparative Example 2 and Example 2 is that the adhesive emulsion B is directly coated on both sides of the PET substrate;
[0055] The specific steps are as follows:
[0056] (1) Add 10 g of ammonium persulfate to 250 g of deionized water and stir for 30 min to obtain an initiator aqueous solution;
[0057] (2) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and stirred for reaction for 6 h to obtain adhesive emulsion B;
[0058] (3) 500 g of adhesive emulsion B was applied to both sides of the PET substrate using an applicator, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain an adhesive tape.
[0059] Comparative Example 3:
[0060] The difference between Comparative Example 3 and Example 2 is that the nano boron nitride is not epoxidized;
[0061] The specific steps are as follows:
[0062] (1) Dispersing 50 g of nano-boron nitride in 100 g of deionized water, and ultrasonicating for 20 min to obtain a nano-boron nitride dispersion;
[0063] (2) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 30 min to obtain an initiator aqueous solution;
[0064] (3) 1 g of sodium dodecyl sulfate and 4 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of styrene, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and then 150 g of nano boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 6 h to obtain adhesive emulsion A;
[0065] (4) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and stirred for reaction for 6 h to obtain adhesive emulsion B;
[0066] (5) 400 g of adhesive emulsion A and 100 g of adhesive emulsion B were mixed, stirred for 15 min, applied to both sides of the PET substrate using an applicator, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain an adhesive tape.
[0067] Comparative Example 4:
[0068] The difference between Comparative Example 4 and Example 2 is that the styrene in step (4) is replaced by n-butyl acrylate;
[0069] The specific steps are as follows:
[0070] (1) Add 2.5 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 30 min, then heat to 50° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 4 h, wash, and dry to obtain epoxidized nano boron nitride;
[0071] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 20 min to obtain an epoxidized nano-boron nitride dispersion;
[0072] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 30 min to obtain an initiator aqueous solution;
[0073] (4) 1 g of sodium dodecyl sulfate and 4 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and then 150 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 6 h to obtain adhesive emulsion A;
[0074] (5) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of n-butyl acrylate, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and stirred for reaction for 6 h to obtain adhesive emulsion B;
[0075] (6) 400 g of adhesive emulsion A and 100 g of adhesive emulsion B were mixed, stirred for 15 min, applied to both sides of the PET substrate using an applicator, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain an adhesive tape.
[0076] Comparative Example 5:
[0077] The difference between Comparative Example 5 and Example 2 is that n-butyl acrylate in step (5) is replaced by styrene;
[0078] The specific steps are as follows:
[0079] (1) Add 2.5 g of silane coupling agent KH-560 to a mixture of 300 g of deionized water and 100 g of anhydrous ethanol, stir for 30 min, then heat to 50° C., add 50 g of nano boron nitride, ultrasonicate for 20 min, stir to react for 4 h, wash, and dry to obtain epoxidized nano boron nitride;
[0080] (2) dispersing 50 g of epoxidized nano-boron nitride in 100 g of deionized water, and ultrasonicating for 20 min to obtain an epoxidized nano-boron nitride dispersion;
[0081] (3) adding 10 g of ammonium persulfate to 250 g of deionized water and stirring for 30 min to obtain an initiator aqueous solution;
[0082] (4) 1 g of sodium dodecyl sulfate and 4 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of styrene, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and then 150 g of epoxidized nano-boron nitride dispersion was added dropwise. After the addition was completed, the mixture was stirred for reaction for 6 h to obtain adhesive emulsion A;
[0083] (5) 1 g of sodium dodecyl sulfate and 5 g of fatty alcohol polyoxyethylene ether AOE-9 were added to 120 g of deionized water, stirred for 30 min, and then 75 g of methyl methacrylate, 300 g of styrene, 100 g of isooctyl acrylate, 20 g of ethyl acrylate and 15 g of hydroxyethyl acrylate were added, stirred for 15 min, heated to 85° C., 130 g of initiator aqueous solution was added, and stirred for reaction for 6 h to obtain adhesive emulsion B;
[0084] (6) 400 g of adhesive emulsion A and 100 g of adhesive emulsion B were mixed, stirred for 15 min, applied to both sides of the PET substrate using an applicator, dried in an oven at 120° C. for 6 h, covered with a release film, and rolled and slit to obtain an adhesive tape.
[0085] Performance Test:
[0086] Initial adhesion: Referring to the national standard GB / T 4852-2002, the initial adhesion of the tape was tested using an initial adhesion tester. The results are shown in Table 1.
[0087] Adhesion: Referring to the national standard GB / T 4851-2014, the adhesion of the tape was tested using an adhesion tester. The results are shown in Table 1.
[0088] Peel strength: Referring to the national standard GB / T2792-2014, the 180° peel strength of the tape was tested using a universal testing machine. The results are shown in Table 1.
[0089] Thermal conductivity: The thermal conductivity of the colloid on the tape surface was measured using a thermal conductivity meter. The results are shown in Table 1.
[0090] High temperature resistance: The sample to be tested is made into a 100mm long and 25mm wide tape, and then the tape is pasted in the middle of the test steel plate, rolled back and forth with a roller for 3 times, and placed in a vacuum drying oven at 150°C for 3 hours, then taken out and cooled to room temperature under natural conditions, and the tape is peeled off from the test steel plate to observe the residual glue on the test steel plate. If there is no residual glue on the test steel plate, it is represented by the number "0"; if there is residual glue but it is not serious, it is represented by the number "1"; if there is residual glue and it is relatively serious, it is represented by the number "2"; if there is residual glue and it is very serious, it is represented by the number "3". The results are shown in Table 1.
[0091] Table 1 Performance test results
[0092]
[0093] Data Analysis:
[0094] It can be seen from the data of Examples 1-3 in Table 1 that the high thermal conductive tape prepared by the present invention has high initial adhesion, sustained adhesion and peel strength, indicating that it has excellent bonding performance, high thermal conductivity and high temperature resistance, and is particularly suitable for LED application scenarios that require efficient thermal management and reliable bonding, such scenarios including but not limited to LED lamps, display screens, backlight modules and LED components in other electronic devices.
[0095] It can be seen from the data of Example 2 and Comparative Example 1 in Table 1 that although the use of adhesive emulsion A alone can slightly increase the thermal conductivity, it greatly reduces the bonding performance. This is mainly because there is a large amount of boron nitride on the surface of the colloid particles in adhesive emulsion A, which makes it difficult to fully adhere to the surface of the substrate, and the poor cohesive force also leads to a decrease in the holding force.
[0096] From the data of Example 2 and Comparative Example 2 in Table 1, it can be seen that although the use of adhesive latex B alone can improve the initial adhesion and peel strength, it reduces the holding force and thermal conductivity, which is mainly due to the decrease in cohesive force and the absence of thermally conductive boron nitride.
[0097] It can be seen from the data of Example 2 and Comparative Example 3 in Table 1 that the epoxidation of the boron nitride surface has a significant effect on the adhesive properties and thermal conductivity of the tape. This is because the epoxy groups on the surface of the epoxidized boron nitride react with the hydroxyl groups of hydroxyethyl acrylate in the adhesive emulsion A on the one hand to wrap the rubber particles and ensure the stability of the rubber particles; on the other hand, in the later thermal curing stage, they react with the hydroxyl groups in the adhesive emulsion B to form a uniform thermal conductive network while improving the cohesive force.
[0098] It can be seen from the data of Example 2 and Comparative Examples 4-5 in Table 1 that the hard monomer styrene and the soft monomer n-butyl acrylate synergistically adjust the adhesive tape's adhesive properties and thermal conductivity, so that the tape has high thermal conductivity and high adhesive properties.
[0099] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A high thermal conductive tape, characterized in that: By weight, 8 parts of adhesive emulsion A and 1-3 parts of adhesive emulsion B are mixed, coated on both sides of a PET substrate, and thermally cured to obtain; The adhesive emulsion A is obtained by emulsion polymerization of the following raw materials in parts by weight: 60-90 parts of methyl methacrylate, 200-400 parts of styrene, 80-120 parts of isooctyl acrylate, 15-25 parts of ethyl acrylate, 10-20 parts of hydroxyethyl acrylate, 100-200 parts of epoxidized nano boron nitride dispersion, 4-6 parts of emulsifier, 100-150 parts of initiator aqueous solution and 80-160 parts of deionized water; The adhesive emulsion B is obtained by emulsion polymerization of the following raw materials in parts by weight: 60-90 parts of methyl methacrylate, 200-400 parts of n-butyl acrylate, 80-120 parts of isooctyl acrylate, 15-25 parts of ethyl acrylate, 10-20 parts of hydroxyethyl acrylate, 4-6 parts of emulsifier, 100-150 parts of initiator aqueous solution and 80-160 parts of deionized water; The preparation method of the epoxidized nano-boron nitride dispersion is as follows: (1) using silane coupling agent KH-560 to modify nano boron nitride to obtain epoxidized nano boron nitride; (2) dispersing the epoxidized nano-boron nitride in deionized water and ultrasonicating for 20-40 minutes to obtain an epoxidized nano-boron nitride dispersion; In the step (1), the weight ratio of silane coupling agent KH-560 to nano boron nitride is 1-5:50; In the step (2), the weight ratio of epoxidized nano-boron nitride to deionized water is 1:
2.
2. The high thermal conductive tape according to claim 1, characterized in that: The emulsifier is a mixture of sodium dodecyl sulfate and fatty alcohol polyoxyethylene ether in a weight ratio of 1:3-5.
3. The high thermal conductive tape according to claim 1, characterized in that: The preparation method of the initiator aqueous solution is as follows: adding ammonium persulfate into deionized water and stirring for 20-40 minutes to obtain the initiator aqueous solution.
4. The high thermal conductive tape according to claim 3, characterized in that: The weight ratio of the ammonium persulfate to deionized water is 1:
25.
5. The high thermal conductive tape according to claim 1, characterized in that: The preparation method of the adhesive emulsion A is as follows: add an emulsifier into deionized water, stir for 20-40 minutes, then add methyl methacrylate, styrene, isooctyl acrylate, ethyl acrylate and hydroxyethyl acrylate, stir for 10-20 minutes, heat to 80-90° C., add an initiator aqueous solution, then dropwise add an epoxidized nano boron nitride dispersion, and after the dropwise addition is completed, stir and react for 5-7 hours to obtain the adhesive emulsion A.
6. The high thermal conductive tape according to claim 1, characterized in that: The preparation method of the adhesive emulsion B is as follows: add an emulsifier into deionized water, stir for 20-40 minutes, then add methyl methacrylate, n-butyl acrylate, isooctyl acrylate, ethyl acrylate and hydroxyethyl acrylate, stir for 10-20 minutes, heat to 80-90° C., add an initiator aqueous solution, stir and react for 5-7 hours to obtain the adhesive emulsion B.
7. A method for preparing a high thermal conductive tape according to any one of claims 1 to 6, characterized in that: The following steps are involved: Adhesive emulsion A and adhesive emulsion B are mixed, stirred for 10-20 minutes, coated on both sides of the PET substrate with a coater, dried in an oven at 115-125°C for 5-7 hours, covered with a release film, rolled up and slit to obtain a high thermal conductive tape.